(untitled) (El-Wahat Journal for Research and Studies, 2025)
Modern Institutions Have Shown Great Interest In Scientific Studies And Research. It Is The Social Field Within Which Individuals Interact According To A Typical Organizational Structure. Leadership Is One Of The Most Important Organizational Processes, Where The Leader Directs And Influences The Behavior Of Individuals To Achieve Their Goals, In The Presence Of Organizational Communication. The University Is A Large Institution With Complex Organizational Structures That Requires Participatory Leadership That Adopts A Communication Culture That Enables It To Continue And Achieve Its Goals. Our Goal In The Study Was To Find Out What Method And Relationships A Democratic Leader Adopts To Enhance The Values ​​And Principles Of Organizational Communication In University Institutions. The Study Hypotheses Are Represented By The Participatory Leadership Style And Human Relations Of The Democratic Leader In Consolidating The Values ​​And Principles Of The Institutional Communication Culture At The University Of Ghardaia. It Was Subjected To A Field Study Using A Questionnaire Form And An Interview Tool. Field Study Is On A Sample Of Employees (Administrative Professors And Administrators). One Of The Most Important Results Obtained Is That The Leader’s Participatory Style And The Nature Of The Human Relations He Enjoys Towards His Subordinates Contribute To Enhancing The Values ​​And Principles Of The Culture Of Organizational Communication In The Ghardaia University Institution. Keywords: Participatory Leadership, Culture, Institutional , Communication.